Field Instrument with HART Interface - Kunz, Jan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
This paper describes design and development of of creating field instrument demonstration module. Module is capable of measuring multiple sensors such as thermocouples, RTD, or pressure sensor, analogue sensor simulation is also provided. Sensor’s side is isolated from output, which is composed of 4 - 20 mA current loop and HART interface. Current loop also provides power supply and module can communicate via HART also when alarm current (3,2 mA) is set. Basic safety features like open wire detection, over and undervoltage protection are also implemented.
Keywords: current loop; HART; thermocouple; RTD; pressure sensor